Protectin DX Relieve Hyperoxia‐induced Lung Injury by Protecting Pulmonary Endothelial Glycocalyx - Liang Z; Yue H; Xu C; Wang Q; Jin S (Dove Medical Press, 2023)
Zhongjie Liang,1,2 Huilin Yue,1 Congcong Xu,1 Qian Wang,3 Shengwei Jin2,3 1Department of Neonatology, The Second Affiliated Hospital, Yuying Children's Hospital of Wenzhou Medical University, Zhejiang, People's Republic of China; 2Department of Anesthesia and Critical Care, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, Zhejiang, People's Republic of China; 3Key Laboratory of Anesthesiology of Zhejiang Province, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, Zhejiang, People's Republic of ChinaCorrespondence: Qian Wang; Shengwei Jin, Department of Anesthesia and Critical Care, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, 109 Xueyuan Road, Wenzhou, Zhejiang Province, 325027, People's Republic of China, Tel +86 577-88002806, Fax +86 577-88832693, Email wqian84@163.com; jinshengwei69@163.comBackground: Bronchopulmonary dysplasia (BPD) is a common chronic lung disease in premature infants with limited treatments and poor prognosis. Damaged endothelial glycocalyx leads to vascular permeability, lung edema and inflammation. However, whether hyperoxia increases neonatal pulmonary microvascular permeability by degrading the endothelial glycocalyx remains unknown.Methods: Newborn mice were maintained in 60- 70% O2 for 7 days. Protectin DX (PDX), an endogenous lipid mediator, was injected intraperitoneally on postnatal d 0, 2, 4 and 6. Lung samples and bronchoalveolar lavage fluid were taken at the end of the study. Primary human umbilical vein endothelial cells (HUVECs) were cultured in 80%O2.Results: Hyperoxia exposure for 7 days led to neonatal mice alveolar simplification with less radial alveolar count (RAC), mean linear intercept (MLI) and mean alveolar diameter (MAD) compared to the control group. Hyperoxia exposure increased lung vascular permeability with more fluid and proteins and inflammatory factors, including TNF-α and IL-1β, in bronchoalveolar lavage fluid while reducing the heparan sulfate (HS), the most abundant component of the endothelial glycocalyx, in the pulmonary endothelial cells. PDX relieve these changes. PDX attenuated hyperoxia-induced high expression of heparanase (HPA), the endoglycosidase that shed endothelial glycocalyx, p‐P65, P65, and low expression of SIRT1. BOC‐2 and EX527 abolished the affection of PDX both in vivo and intro.Conclusion: In summary, our findings indicate that PDX treatment relieves hyperoxia‐induced alveolar simplification, vascular leakage and lung inflammation by attenuating pulmonary endothelial glycocalyx injury via the SIRT1/NF‐κB/ HPA pathway.Keywords: bronchopulmonary dysplasia, endothelial glycocalyx, inflammation, protectin DX